The Effects of Leadership Styles on Organizational Innovation in Universities in Indonesia and Malaysia - Siswanto; Achmad Sani Supriyanto; Eko Suprayitno; Vivin Maharani Ekowati; Agus Eko Sujianto; Fuadah Binti Johari; Ali Ridlo; Abd Haris; Muhtadi Ridwan (Behavioral Science Research Institute (BSRI), 2024)
Indexed by Scopus